How attitudes of state and community leaders regarding health equity and social determinants of health are associated with behavioral intentions to improve population health. - Nyna Williams; Emily Newton-Hoe; Martha Kovac (PLoS ONE, 2024)
A critical driver of population health, well-being, and equity is making health a shared value, or the belief that health is a priority for oneself and one's community. For people in positions of influence, attitudes regarding their organization's perspective may result in decisions that advance health equity or reinforce inequities. Yet despite the potential role of leaders in influencing health and well-being, little is known about their attitudes regarding their organization's perspective on what shapes health, or how their attitudes translate into actions that improve population health. The objectives of this study are twofold: (1) to understand leaders' attitudes with regard to their organization's perspective on population health and (2) to identify the attitudes associated with leaders' perspectives regarding their organization's intention to engage in behaviors that advance population health. We designed a survey instrument grounded in the Theory of Planned Behavior and fielded the survey to 18,367 state and community leaders across all 50 U.S. states, 325 U.S. cities, and nine sectors from fall 2020 until spring 2022. We received surveys from 5,450 leaders, yielding a 32 percent response rate. Survey respondents viewed social determinants of health and health equity as important factors influencing population health. Additionally, two attitudes were most associated with leaders' intentions to promote population health-"self-efficacy" (a leader's confidence in taking action to promote health for all) and "behaviors valued by important others" (how much certain groups want the organization to take action that promotes health for all). Efforts to improve population health through leaders should focus on supporting leaders' self-efficacy and on increasing leaders' perceptions regarding behaviors valued by important others. Governmental entities and funders can use these data to support leaders' efforts in improving population health, well-being, and equity.